Human-Animal Reincarnation and Animal Grief in Kabbalah: Joseph of Hamadan’s Contribution - Sachs-Shmueli, Leore (The journal of Jewish thought & philosophy, 2023)
In thirteenth-century Castile, the kabbalist R. Joseph of Hamadan offered an unprecedented articulation of the idea of reincarnation (gilgul), proposing that Jewish men could be reborn as gentiles, women, or even animals. This article studies the formation of the Jewish belief in the transmigration of human souls into animal bodies, focusing on the question of animal pain. It contextualizes the kabbalistic literary treatment of animals by examining the thirteenth-century European genre of bestiaries, which attempted to instill proper morals in readers by associating animals with sinners. Although the idea of animal reincarnation led kabbalists to treat animals as creatures with human souls, it did not lead to a fundamental or radical shift in the treatment of animals.